2014
DOI: 10.1111/vco.12117
|View full text |Cite
|
Sign up to set email alerts
|

Predicting clinical outcome in feline oral squamous cell carcinoma: tumour initiating cells, telomeres and telomerase

Abstract: Feline oral squamous cell carcinoma (SCC) has very poor prognosis. Here, a retrospective pilot study was conducted on 20 feline oral SCC patients who underwent stereotactic radiation therapy (SRT), to evaluate: (1) the value of putative tumour initiating cell (TIC) markers of human head and neck SCC (CD44, Bmi-1); (2) telomere length (TL) specifically in putative TICs; and (3) tumour relative telomerase activity (TA). Significant inverse correlations were found between treatment outcomes and Bmi-1 expression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 56 publications
2
12
0
1
Order By: Relevance
“…Its catalytic subunit TERT is overexpressed in many human and animal tumors; however, studies regarding expression of TERT and telomerase activity in FOSCC are scarce (18,31). Here, we show, for the first time, TERT expression and telomerase activity in FOSCC-derived cell lines SCCF2 and SCCF3, in agreement with a unique study reporting functional enzymatic activation in FOSCC samples: this suggests that telomerase may play a role in neoplastic process in these tumors as shown in human and canine counterpart (2,3,21,41). In cancer, different factors may influence the degree of telomerase activity, such as expression levels of TERT, TERT sub-cellular localization, or tissue origin of the lesion (40,42).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Its catalytic subunit TERT is overexpressed in many human and animal tumors; however, studies regarding expression of TERT and telomerase activity in FOSCC are scarce (18,31). Here, we show, for the first time, TERT expression and telomerase activity in FOSCC-derived cell lines SCCF2 and SCCF3, in agreement with a unique study reporting functional enzymatic activation in FOSCC samples: this suggests that telomerase may play a role in neoplastic process in these tumors as shown in human and canine counterpart (2,3,21,41). In cancer, different factors may influence the degree of telomerase activity, such as expression levels of TERT, TERT sub-cellular localization, or tissue origin of the lesion (40,42).…”
Section: Discussionsupporting
confidence: 89%
“…Feline OSCC (FOSCC) is considered a spontaneous animal model of human counterpart, since several biological properties are shared between tumors of the two species, including activation of cancer-related molecular pathways and prognostic markers (19,20). However, there is only one report describing telomerase activity in FOSCC samples and studies regarding expression of TERT and its correlation with enzymatic activity in these types of cancer are lacking, particularly in tumor-derived living cells (21). Similarly, despite their high invasive potential, expression of MMPs in FOSCC has never been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of EGFR is among the non-canonical functions of TERT (2), and interestingly, previous studies report a significant correlation between EGFR expression and levels of TA in FOSCC samples (20). Consistently, here, BIBR1532 induced downregulation of EGFR and its downstream effector pERK in all cell lines, confirming its functional correlation with TERT in FOSCC also in vitro.…”
Section: Discussionsupporting
confidence: 88%
“…However, several authors found that acute treatment with BIBR1532 is not sufficient to obtain a substantial telomeres attrition; instead, it induces direct random DNA damage, likely due to the inhibition of extra-telomeric functions of TERT in DNA repair processes rather than to disable its canonical activity at telomeres (12). Moreover, in FOSCC samples, lower TA does not correspond to shorter telomeres, possibly due to the activation of mechanisms of alternative lengthening of telomeres (ALT) (20). In this study, we did not measure telomeres length upon treatment and cannot exclude the occurrence of ALT in SCCF cells; however, our data demonstrate that, whatever the cellular and molecular mechanisms involved, BIBR1532 exerts potent tumor growth suppressive activities in FOSCC (see Supplementary Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation